The Active Energy Consumer in EU Law. (5th April 2018) - CSERES, KJ
Abstract: With the availability of cheaper technology and the rise of digitalisation, consumers can actively participate in markets and also offer their own services or self-/co-produce products and services. Active consumers are fundamental building-blocks of the European Union's goal to achieve smart, sustainable and inclusive growth in Europe. In the energy sector active consumers play a key role in promoting competition, ensuring affordable energy prices and security of supply, as well as contributing to the EU's environmental and climate goals. By engaging in more efficient energy use, consumers are crucial actors to manage the energy transition. However, the present legal framework does not fully facilitate this active role. The aim of this article is to answer the question how EU law conceptualises and supports the active role of consumers in the regulation of energy markets.